The Role of Leaders in Formulation of the Foreign Policy Identity in Egypt - I. E. Ibragimov (Vestnik MGIMO-Universiteta, 2021)
The features of the formation of the of the state explains the high level of interest in this scientific problem in the modern theory of international relations. The study of for eign policy identity is capable of providing an understanding of the policy-making activity of the state and its positioning in the international arena. The process of forming a foreign policy identity linked to both objective and subjective factors. The objective factors should be classified as geographical, historical, cultural and religious, the key subjective factors can be considered the role of a leader. This factor is standard for Middle Eastern states, especially for Egypt, where there are traditions of strong centralized powers. Egyptian leaders have supreme power in foreign policy decisions within the framework of the political system. Egypt's foreign policy is often determined by the personal character traits of the country's leaders. This article aims to study the role of the head of the Egypt in the search for foreign policy identity in the context of an identity crisis at the national level. Egypt has a long history of authoritarian rule, because it is impossible to separate national identity from foreign policy identity. Since its independent existence, each period with its own context established a different framework of identity and worldview for decision-makers in the field of Egypt`s foreign policy. The predominance of various elements in ideological as well as worldview in the age of the rule of a particular president has led to noticeable differences in Egypt's foreign policy at the current stage. This article attempts to answer the following research questions: What place does of the institute of the heads of State in foreign policy decisions? How leader's influence does determine the foreign policy role of the state? What changes in foreign policy priorities have taken place during the analysis period? What are the reasons for the differences between the main periods of Egypt's foreign policy in goals, tools and approaches to the outside world? The author comes to the conclusion that the change of the political leader plays an important role in the transformations of Egypt's foreign policy. The article analyzes the main trends in the foreign policy self-perception of Egypt in order to confirm the hypothesis that the foreign policy identity of Egypt had not evolved a discontinuity even in the conditions of dramatic events, whether it is the Arab-Israeli conflict, the Peace treaty with Israel or the events of the Arab Spring.